2013
DOI: 10.1111/imm.12154
|View full text |Cite
|
Sign up to set email alerts
|

A cytokine‐controlled mechanism for integrated regulation of T‐lymphocyte motility, adhesion and activation

Abstract: SummaryThe co-ordination of T-cell motility, adhesion and activation remains poorly understood. It is also unclear how these functions are co-ordinated with external stimuli. Here we unveil a series of molecular interactions in cis at the surface of T lymphocytes with potent effects on motility and adhesion in these cells, and communicating with proliferative responses. These interactions were controlled by the signature cytokines of T helper subsets interleukin-2 (IL-2) and IL-4. Low-density lipoprotein recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 60 publications
11
55
0
Order By: Relevance
“…These results confirm and extend previous findings that T‐cell motility is regulated by a counteradhesive motogenic mechanism directed by LRP1 and endogenous TSP‐1 . One important conclusion that can be drawn from the effects of ustekinumab is that motility and adhesion/spreading most likely are regulated at the cell surface level (Figs ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results confirm and extend previous findings that T‐cell motility is regulated by a counteradhesive motogenic mechanism directed by LRP1 and endogenous TSP‐1 . One important conclusion that can be drawn from the effects of ustekinumab is that motility and adhesion/spreading most likely are regulated at the cell surface level (Figs ).…”
Section: Discussionsupporting
confidence: 90%
“…The inhibitory effect on T‐cell motility of LRP1 knockdown coupled to enhancement of adhesion was previously shown to be mimicked by an inhibitor of the Janus kinase–signal transducer and activator of transcription 1 (JAK/STAT) pathway . The present results showed that ustekinumab mimicked LRP1 silencing and inhibition of the JAK/STAT pathway in its effects on motility and adhesion as well as in the enhancing effect on the expression of intact TSP‐1.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Their association on PMN disrupts binding of CRT to LRP1 on macrophages and impairs CRT-LRP1-mediated phagocytosis (26). Moreover, LRP1 was shown to involve regulating T cell motility (27). Therefore we sought to determine whether mP3-expressing PMN-mediated T cell inhibition involved LRP1 on T cells.…”
Section: Resultsmentioning
confidence: 99%
“…While the anti-CD47 mAb B6H12 disrupts the interaction between CD47 and SIRPα, it can also affect the binding of CD47 to SIRPγ (31) and thrombospondin1 (TSP1) (32). This implies that anti-CD47 therapy might involve functions of CD47 that are independent from SIRPα, which also provides an alternative explanation to the efficacy of CD47 shRNA (17).…”
Section: Sirpα-independent Functions Of Cd47mentioning
confidence: 99%